Effect of periodontal treatment in patients with periodontitis and diabetes: systematic review and meta-analysis - Mauricio Baeza; Alicia Morales; Carlos Cisterna; Franco Cavalla; Gisela Jara; Yuri Isamitt; Paulina Pino; Jorge Gamonal
Abstract The evidence is inconclusive regarding the effect of periodontal treatment on glycemic control and systemic inflammation in patients with type 2 diabetes (T2D) and periodontitis Objective: To evaluate the effect of scaling and root planing (SRP) on the metabolic control and systemic inflammation of patients with type 2 diabetes (T2D). Methodology: A literature search was conducted using the MEDLINE database via PubMed and the Cochrane Central Register of Controlled Trials, from their oldest records up to July 2018. Only randomized clinical trials (RCT) were considered eligible for evaluating the effect of periodontal treatment on markers of metabolic control [glycated hemoglobin (HbA1C)] and systemic inflammation [C-reactive protein (CRP)] in patients with T2D. The quality of the studies was evaluated using the Cochrane Collaboration risk assessment tool. Meta-analyses were performed for HbA1c and CRP using random effects models. The size of the overall intervention effect was estimated by calculating the weighted average of the differences in means (DM) between the groups in each study. Heterogeneity was assessed using the Q-statistic method (x2 and I²). The level of significance was established at p<0.05. Results: Nine RCT were included. SRP was effective in reducing HbA1c [DM=0.56 (0.36-0.75); p<0.01] and CRP [DM=1.89 (1.70-2.08); p<0.01]. No heterogeneity was detected (I2=0%, p>0.05). Conclusions: SRP has an impact on metabolic control and reduction of systemic inflammation of patients with T2D.